1992
DOI: 10.1557/proc-283-463
|View full text |Cite
|
Sign up to set email alerts
|

Microcrystalline Silicon in a-SI:H Based Multljunction Solar Cells

Abstract: Materials issues central to the application of microcrystalline silicon (μc-Si) doped layers in a-Si:H based solar cells are discussed, which include: (1) characterization of ultra-thin layers to be incorporated in the device, and (2) methods to promote nucleation of μc-Si on desired substrates within a thickness on the order of ∼100Å. Successful application of (μc-Si) in multijunction a-Si:H based solar cells are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…1,7,27 We also observed this phenomenon for the films grown at different frequencies on glass and a-Si:H. In Fig. 6 the thickness dependence of the conductivity of cSi:H films on glass and a-Si:H is shown for material prepared at two different plasma excitation frequencies.…”
Section: B Electrical Conductivitysupporting
confidence: 53%
See 1 more Smart Citation
“…1,7,27 We also observed this phenomenon for the films grown at different frequencies on glass and a-Si:H. In Fig. 6 the thickness dependence of the conductivity of cSi:H films on glass and a-Si:H is shown for material prepared at two different plasma excitation frequencies.…”
Section: B Electrical Conductivitysupporting
confidence: 53%
“…The use of microcrystalline silicon in this recombination junction leads to a significant improvement of the device. 1 A further important application of c-Si:H will be as an active layer in stacked solar cells or as an all-thin-crystalline solar cell where an improved red response and a presumably higher stability with respect to a-Si:H are the key issues. 2 There are two major technical problems in the engineering of microcrystalline silicon: ͑1͒ a very low deposition rate and ͑2͒ a strongly substrate dependent nucleation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…1 -The absorption coefficient was calculated based on dualbeam transmittance measurements on a Cary, Inc. spectrophotometer and an awLiliary measurement of the thickness using a mechanical profilometer. For comparison purposes we have also shown literature curves (Yang, Chen, Wiedeman, and Catalano, 1993) for the absorption cuefficients for severalp+ materials currently used in a-Si:H based cells.…”
Section: Our Films Werementioning
confidence: 99%
“…Alternatively, at least one of the n ϩ , p ϩ layers should be microcrystalline to achieve the same objective. [2][3][4][5][6] It has also been suggested that electrons from the n ϩ side and holes from the p ϩ side are partly driven towards this junction under the influence of the electric field in the respective subcells; and partly ''tunnel'' towards this junction against the high opposing n ϩ /p ϩ field. Computer simulation of such structures 1,7 has shown that conduction band edge grading of the subcell on the n ϩ side and valence band edge grading of the subcell on the p ϩ side, to simulate the real tunneling of electrons and holes, respectively, to the junction region are essential to simulate the high V oc and FF of tandem solar cells.…”
Section: Introductionmentioning
confidence: 99%